Transfer Pricing and Tunneling: Moderating Role of Female Directors in Indonesian Perspective - Destian Villania Putri; Elva Nuraina; Nur Wahyuning Sulistyowati (Faculty of Economics, Universitas Sriwijaya, 2026)
This study aims to examine the effect of transfer pricing on tunneling practices by considering the role of female directors as a moderating variable. Using a quantitative approach with a sample of 265 observations of non-financial companies listed on the Indonesia Stock Exchange for the 2019–2023 period, this study applies linear regression analysis and Moderated Regression Analysis (MRA). The results show that transfer pricing has no significant effect on tunneling. However, female directors have been shown to significantly moderate the relationship by strengthening oversight mechanisms, therebysuppressing the potential for tunneling. This study's contribution lies in integrating agency theory and gender diversity to explain companies' opportunistic behavior in developing countries. In practice, these findings emphasize the importance of gender diversity in strengthening corporate governance and reducing the risk of financial policy abuse.